A tragedy revealed the story of the Italian population of Istria, Dalmatia, and Venezia Giulia, 1943-1956 - Petacco, Arrigo 1929- (University of Toronto Press, 2020)
"As the Second World War drew to a close, European borders were being redrawn. The regions of Istria, Dalmatia, and Venezia Giulia, nominally Italian but at various times also belonging to Austria and Germany, fell under the rule of Yugoslavia and its dictator Marshal Tito. The ensuing removal and genocide of Italians from these regions had been little explored or even discussed until 1999, when the esteemed Italian journalist Arrigo Petacco wrote L'esodo: La tragedia negata degli italiani d'Istria, Dalmazia e Venezia Giulia. Now this story is available in English as A Tragedy Revealed. Petacco explains the history of the regions and how they were shifted between empires for centuries. The greater part of the story however details the genocidal program of the Yugoslav Communist government toward the native Italians in the regions. Based on previously unavailable archival documents and oral accounts from people who were there, Petacco reveals the events and exposes the Italian government's mishandling--and then official silence on--the situation. This is a riveting work on a little-known, tragic event written by one of Italy's most highly regarded journalists."--
Reprint. Translation originally published: Toronto : University of Toronto Press, 2005
Keywords: Geschichte 1943-1956; Italiener; Julisch-Venetien; Dalmatien; Istrien; Italians / Istria (Croatia and Slovenia) / History / 20th century; Italians / Croatia / Dalmatia / History / 20th century; World War, 1939-1945 / Territorial questions / Italy; World War, 1939-1945 / Territorial questions / Yugoslavia; Istria (Croatia and Slovenia) / History / 20th century; Dalmatia (Croatia) / History / 20th century; Friuli Venezia Giulia (Italy) / History / 20th century; Friuli Venezia Giulia (Italy) / Politics and government / 20th century; Italians; Politics and government; Croatia / Dalmatia; Europe / Istria; Italy; Italy / Friuli Venezia Giulia; Yugoslavia; 1900-1999; History